Perencanaan Sistem Penyediaan Air Minum Di Kecamatan Pangkalan Lesung Kabupaten Pelalawan - Nurul Annisa; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Clean water services in Pangkalan Lesung Subdistricts in Pelalawana Regency still relies from bottle water, boreholes, river water, springs and rainwater, the quality and quantity of these sources not quaranteed. The need for water in Pangkalan Lesung District in 2038 reaches 144,24 l/sec. so it is necessary to plan a drinking water supply system for the next 20 years using raw water from the Kuyo River. Based on th mass balance analysis, it is found that units capable of processing raw water with water quality are in accordance withPERMENKES number 492 in 2010. The processing unit are planned for intake, pre-sedimentation, neutralization, coagulation, flocculation, sedimentation, filtration, disinfection and reservoar is useful for waterstorage before distribution. The volume of reservoar required is 1869,3 m3and need to do the addition of the distribution pump with capacity is 60 l/s and head pump is 55 m to drain the water to service area. The creationof a distribution network using the software EPANET 2.0 with trial and error in inserting the value of the pipe diameter so that it meets the technical criteria for design. The budget required for planning a drinking watersupply system in Pangkalan Lesung District is Rp. 79.969.000.000,-Keyword: Pangkalan Lesung, Water Requirements, Production Units, EPANET 2.0, Distribution.